Exploring the Role of Influencer Marketing and Word of Mouth on Purchasing Decisions with Consumer Trust as a Moderating Variable: Quantitative Analysis Study on E-Commerce Market in Banten Province, Indonesia - Supriadi, Asep (Westscience Press, 2023)
This study explores the complex relationships between word-of-mouth, customer trust, influencer marketing, and their combined effects on buying decisions in Banten's e-commerce markets. Data from 195 online shoppers were examined using Structural Equation Modelling with Partial Least Squares (SEM-PLS). The study finds a strong correlation between consumer trust, word-of-mouth, influencer marketing, and purchase decisions. One key component that emerged was consumer trust, which moderated the impact of word-of-mouth and influencer marketing on purchase decisions. The results provide useful information for companies looking to maximize marketing plans in the particular setting of Banten's e-commerce environment.